The prospect of the utilization of Non-Timber Forest Products from Setulang Village forest based on local knowledge of the Uma Longh community in Malinau, North Kalimantan, Indonesia - THOMAS R. HUTAURUK; ABUBAKAR M. LAHJIE; B.D.A.S. SIMARANGKIR; MARLON I. AIPASSA; YOSEP RUSLIM (Biodiversitas Journal of Biological Diversity, 2018)
Hutauruk TR, Lahjie AM, Simarangkir B.D.A.S., Aipassa MI, Ruslim Y. 2018. The prospect of the utilization of Non-Timber Forest Products from Setulang Village forest based on local knowledge of the Uma Longh community in Malinau, North Kalimantan, Indonesia. Biodiversitas 19: 421-430. The establishment of Village Forest status gives local people assurance to manage the forest independently, but also limits its utilization. Communities are given freedom in the utilization of Non-Timber Forest Products (NTFPs) and environmental services, but they are prohibited to utilize timber forest products that can disturb and destroy the life of flora and fauna in it. The Uma Longh community utilize NTFPs to meet the needs for food, medicines, and craft material. The objective of this study was to know the prospect of the utilization of NTFPs from Setulang Village Forest. Data were gathered by interview, FGD, documentation, observation and field sampling in transects. The analysis method used in this research was CLAPS (Arquiza 2008; Bakkegaard et al. 2016). This research concluded that the NTFPs in Uma Longh community had good prospect so that the commodities included in the NTFPs category could be managed by the local community independently and sustainably, including Calamus sp. and Gigantochloa sp. In order for NTFPs to be available sustainably, the existence of village forest should be maintained, and this requires (i) the existence of government regulatory support that ensures its sustainability, (ii) the community support to comply with agreements and rules made, (iii) the availability of responsible management institutions, and (iv) the availability of adequate funding sources.